Evaluasi Prosedur Pelayanan Kartu Tanda Penduduk Elektronik di Kantor Camat - Qhilby, Qhilby; Tarigan, Usman; Dewi, Rosmala (Universitas Medan Area, 2017)
Seeing the condition of today's society, there are still many complaints in terms of services they get from the government about the low quality of current services. As the spearhead to carry out direct services to the public should each district and government officials to have the capability in carrying out their duties as set by government agencies. Likewise with the subdistrict of Medan Belawan is expected to further? improve ?the ?quality ?of ?the ?performance ?of ?the ?apparatus ?as? to ?which ?has? been ?set ?by ?the government in the service of society. In this case the formulation of the problem is how the procedure for obtaining the Electronic ID card in District Office District of Medan Belawan. The purpose of this study was to determine how the service procedure specified in the management of Electronic Identity Card at the District Office District of Medan Belawan. The method in this research is qualitative by using observation technique, interview and documentation. Based on these results and continue to analyze the data obtained, then the result is evaluation of Electronic Identity Card service procedures at the District Office District of Medan Belawan be quite good. Can be seen with Electronic ID card service provided is in accordance with the procedure for obtaining a KTP Electronics, but only time in the administration which is not in accordance with standard operating procedures.